Bilateral investment treaties in the Western Hemisphere (OAS WashingtonUS, 1996)
Covers the key provisions of 32 bilateral investment treaties within the Western Hemisphere.
A compendium prepared for the Free Trade Area of the Americas Working Group on Investment